Latin American research on breast implant-associated anaplastic large cell lymphoma: mapping and bibliometric analysis: Investigación latinoamericana sobre linfoma anaplásico de células grandes asociado a implantes mamarios: mapeo y análisis bibliométrico - Castrillón-Ospina , Diana Isabel (2024)
Objective: To analyze the scientific evolution of research on breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) in Latin America over the last 10 years. Methods: A cross-sectional bibliometric study was conducted using Scopus as the data source for analysis. Trends and patterns in research were described and characterized, and research metrics and impact indicators were calculated. Results: A total of 46 documents met the inclusion criteria, covering the time period between 2014 and 2023. Of the total documents, 41.3% (n=19) were original articles, followed by 23.9% (n=11) correspondence papers. The annual growth rate was 24.14%. Approximately 82% of the authors published only one article. Brazil led the regional scientific output, whereas Chile showed the highest frequency of prolific authors. Modest global collaboration was observed, with a notable degree of author endogamy. Conclusions: Scientific production on BIA-ALCL remains low compared with other surgical and non-surgical topics in the region. Most of the scientific output has been generated in Brazil, which also maintains a notable collaboration network with the United States and several European countries. Chile has the highest number of prolific authors despite its relatively low overall production. There is a need to promote and design a strategic research agenda that encourages high-quality original research and accelerates, particularly translational, research to advance precision medicine in Latin America.